FUNCTION - Abdullayev Nurbek Shuhrat o‘g'li; Ro'ziqulov Sa'dulla Egamnazar o‘g‘li; Yoʻldoshev Bekmirza Shuxrat oʻgʻli (American Journals, 2024)
The article explains information about the function used in mathematics through examples.
Keywords: Function, law, set, number, equation, graph.